Legal Responsibility of Substitute Doctors Who Do Not Yet Have a License to Practice - Arif, Junaidi (International Journal of Law, Environment, and Natural Resources, 2022)
The purpose of the need for a Practice License for a doctor is, Protection for the public and health workers, if the practice of medicine causes adverse effects on the physical, mental health or life of the patient. Then it becomes a guide for health workers in providing services to the community must have qualifications, competence, and licenses or legality, as well as community empowerment, professional organizations & existing institutions. This study aims to find out how the authority and legal consequences of substitute doctors who do not have a license to practice against the patient's losses. In this writing, the method used by the author is a type of normative legal research. Using laws and regulations and other relevant reference materials, then analyzed with applicable laws relating to the practice of doctors without a license to practice. The result of this study is the service for obtaining licenses for medical practice should be disseminated to the wider community so that the public knows how to take care of licensing, especially doctor's licenses and the service for obtaining licenses for medical practice should be disseminated to the wider community so that the public knows how to take care of licensing, especially doctor's licenses.